Synergistica activation of NF-κB by functional cooperation between Vav and PKCθ in T lymphocytes - Dienz, Oliver; Dröge, Wulf (The journal of biological chemistry, 2000)
Here we identified PKCθ as an activator of transcription factor NF-κB in T cells. PKCθ-induced NF-κB activation was synergistically augmented by Vav. Several experimental approaches revealed that PKCθ is located downstream from Vav in the control of the pathway leading to synergistic NF-κB activation. In addition to the synergistic activation cascade, Vav also triggered NF-κB activity on a separate route. CD3/CD28-induced activation of NF-κB was inhibited by dominant negative forms of Vav or PKCθ, revealing their essential role in this activation pathway. The Vav/PKCθ-mediated signals preferentially activated IκB kinase β. Vav and PKCθ were found to be constitutively associated in unstimulated T cells. Only the ligation of the costimulatory CD28 receptor, but not of the T cell receptor, resulted in the transient dissociation of the Vav-PKCθ complex. In contrast, T cell receptor/CD28 costimulation resulted in faster dissociation and slower reassociation kinetics.
Gesehen am 03.02.2021